Justice, institutions, and luck the site, ground, and scope of equality - Tan, Kok-Chor, 1964- (Oxford : Oxford University Press, 2012)
Kok-Chor Tan addresses three key questions in political philosophy: Where does distributive equality matter? Why does it matter? And among whom does it matter? He argues for an institutional site for egalitarian justice, a luck-egalitarian ideal of why equality matters, and a global scope for distributive justice.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Equality before the law